GLOBAL TECTONICS SINCE THE BREAKUP OF PANGEA 180 MILLION YEARS AGO: EVOLUTION MAPS AND LITHOSPHERIC BUDGET - Weijermars R. (My University, 1989)
Pangea, the Earth's youngest single supercontinent, broke up 180 million years ago. Tectonic plates were subsequently formed by dispersal of the continental fragments and accretion of new oceanic lithosphere. The configurations of all the major lithospheric plates at 0, 20, 65, 95, 140, 180 Ma BP are reconstructed on six globes of the Earth, each with a radius of 10 cm. It appears that plate boundaries maintain a remarkably close fit on model globes of constant radii if the reconstructions include the recovery of subducted spreading patterns. This is illustrated with maps in equatorial orthographic, oblique orthographic and transverse Hammer-Aitoff projections. The snug fit of the tectonic plates at every tested time since the breakup of Pangea 180 Ma BP is consistent with the theory of plate tectonics on a non-expanding Earth and contradicts rapidly expanding Earth models.